Exploring the dynamic earth - Michelle K. Hall-Wallace
The guide leads students through a set of exercises in which they are asked to explore, analyze, and then elaborate on the information extracted from a robust GIS dataset using ArcView, the dominant GIS software tool in the school and college market. The GIS information has been preprocessed into maps and legends, and some ArcView procedures have been automated so students can focus on the science content. Extensive classroom testing at both the college and high school levels shows that students have little difficulty using the ArcView data sets to perform the exercises. Show More Show Less